Finance Performance: Reinvestigation through Intellectual Capital and Good Corporate Governance - Fitri Anista Dewi; Barianto Nurasri Sudarmawan (Maliki Islamic Economics Journal, 2022)
Intellectual Capital (IC) management needs to be carried out in banking because knowledge is an important need for a company whose operational activities directly interact with customers, so existing human resources must have adequate capabilities and knowledge. In addition to knowledge management, implementing Good Corporate Governance (GCG) to create company efficiency and reduce conflicts that arise provides transparency and legitimacy of company activities. This study aims to determine the influence of IC development on the financial performance of Islamic banking and to determine the impact of implementing GCG on the financial performance of Islamic banking in Indonesia. The results showed that simultaneously the variables of IC and GCG had a significant effect on financial performance (ROA). These findings indicate that Islamic banks need to manage knowledge sourced from their employees. In addition, this finding also explains that Islamic banking in Indonesia needs to consider the determination of the number of directors to maximize the duties and responsibilities of the directors in Islamic banking supervision.